MODELING AND ANALYSIS OF DISC BRAKE IN AUTOMOBILES - Hayder (Journal of Mechanical Engineering Research and Developments, 2018)
Brake system is the one of the most significant components in modern automobiles. Its duty is reducing the speed of the vehicle and stops it. Disc brake changes the kinetic energy of rotating parts (wheels) to the heat and dissipated it to air. In this paper the disc brake is modeled and simulated with specific dimensions and analysis it with Finite Elements software (ANSYS R16.1). Two materials were chosen for the disc brake, the Grey Cast Iron and Carbon-Ceramic. Comparison can be done with temperature distribution, deformation and stress and choose the best material. The results showed the Carbon-Ceramic can withstand the thermal stress and approximately there is no deformation for it. Carbon-Ceramic is preferred for disc brake to achieve better performance.